Interaction effects on galaxy pairs with Gemini/GMOS- I: electron density - Krabbe, A. (2014)
We present an observational study about the impacts of the interactions on the electron density of HII regions located in seven systems of interacting galaxies. The data consist of long-slit spectra in the range 4400-7300 A, obtained with the Gemini Multi-Object Spectrograph at Gemini South (GMOS-S). The electron density was determined using the ratio of emission-lines [S II] lambda 6716/ lambda 6731. Our results indicate that the electron density estimates obtained of HII regions from our sample of interacting galaxies are systematically higher than those derived for isolated galaxies. The mean electron density values of interacting galaxies are in the range of Ne = 24 - 532 cm^{-3}, while those obtained for isolated galaxies are in the range of Ne = 40 - 137 cm^{-3}. Comparing the observed emission lines with predictions of photoionization models, we verified that almost all the HII regions of the galaxies AM1054A, AM2058B, AM2306B have emission lines excited by shocks, such as in AM2322B (one point) and AM 2322A (four points). No correlation is obtained between the presence of shocks and electron densities. Indeed, the highest electron density values found in our sample do not belong to the objects with gas shock excitation. We emphasize the importance of considering theses quantities especially when the metallicity is derived for this type of systems.